2011
DOI: 10.2135/cropsci2010.12.0710
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Phenotypic Evaluations with a Molecular Diversity Assessment of a Brazilian Collection of Common Bean Landraces

Abstract: Common bean {Phaseotus vulgaris L.) is the most important legume crop for direct human consumption in Brazil. Overall patterns of genetic diversity of common bean in the country are not well understood. Hence, this study sought to integrate morphological and agronomic evaluations with prior molecular diversity data from a geo-referenced collection of Brazilian common bean. Our sample included 279 randomly chosen landrace accessions from the main growing regions of beans in Brazil. Eighteen morphological and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
4
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 35 publications
8
16
4
5
Order By: Relevance
“…than Mesoamerican accessions. This contrasted with results from other related studies (Asfaw et al, 2009;Burle et al, 2011;Okii et al, 2014 a,b). Such differences may be attributed to differences in genetic samples and respective sampling methods employed.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…than Mesoamerican accessions. This contrasted with results from other related studies (Asfaw et al, 2009;Burle et al, 2011;Okii et al, 2014 a,b). Such differences may be attributed to differences in genetic samples and respective sampling methods employed.…”
Section: Discussioncontrasting
confidence: 97%
“…The considerable presence of admixture and switching of membership in some instances was supported by the PCoA and NJ analyses. These agree with some previous reports (Asfaw et al, 2009;Blair et al, 2010b;Burle et al, 2011;Okii et al, 2014b). In addition, the PCoA and NJ analyses in terms of geographic/ecological sampling of accessions indicated that accessions from different collection sites clustered together, which implied there was significant exchange of planting materials among farmers in different growing regions in the country.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…An intermediate level of genetic diversity was found within common landraces from Brazil when compared to the overall diversity of the species . A significant morphological variability has been verified as well, although not all morphological variability observed for P. vulgaris (BURLE et al, 2011). The study of geo-referenced landraces from Andean and Mesoamerican background revealed the latter was four times more frequent than the former (BURLE et al, 2011).…”
Section: P Vulgaris Is Naturally Distributed In a Wide Area From Normentioning
confidence: 70%
“…The country also holds a huge variety of landraces that have been traditionally cultivated by small farmers over years . There are indications that landraces from the group Mulatinho, in northern Minas Gerais state, have considerable drought tolerance compared with other groups but more studies need to be performed toward its understanding (BURLE et al, 2011).…”
Section: Sources Of Drought Tolerance and Their Selection In Common Beanmentioning
confidence: 99%